2007
DOI: 10.1002/jmri.21213
|View full text |Cite
|
Sign up to set email alerts
|

Rapid multiplanar abdominal survey using MRI with the steady‐state free‐precession technique

Abstract: Purpose: To retrospectively evaluate the sensitivity, specificity, and positive and negative predictive values of steadystate free-precession (SSFP) survey MRI of the abdomen. Materials and Methods:A total of 375 consecutive outpatients underwent abdominal MRI at 1.5T. Excluding diffuse metastatic disease, 110 patients had at least one other clinically important finding. The SSFP survey included contiguous 5-mm-thick axial, sagittal, and coronal slices (total 90 slices) obtained during a total of 90 seconds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…) . SSFP sequences can also be useful in a thick‐slab cinematic format to evaluate myocardial function in cardiac MR and bowel peristalsis in MR enterography …”
Section: Techniques To Minimize Sedation For Pediatric Mri Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…) . SSFP sequences can also be useful in a thick‐slab cinematic format to evaluate myocardial function in cardiac MR and bowel peristalsis in MR enterography …”
Section: Techniques To Minimize Sedation For Pediatric Mri Examinationsmentioning
confidence: 99%
“…41 SSFP sequences can also be useful in a thick-slab cinematic format to evaluate myocardial function in cardiac MR and bowel peristalsis in MR enterography. 18,42 Gradient recalled echo (GRE) imaging is often used for acquiring fast images with T 1 contrast during quiet breathing. 43 2D GRE T 1 -weighted images using a low flip angle are an important part of pediatric abdominal MRI, by characterizing lesions and detecting hemorrhage or fat content.…”
Section: Noise Reductionmentioning
confidence: 99%
“…Anatomical imaging was acquired with the body coil and Fast Imaging Employing Steady-state Acquisition (FIESTA) sequence [28] (field of view = 30 cm, flip angle = 45°, echo/repetition time = 1.71 ms/3.849 ms). CSI data were acquired using elliptic-FIDCSI pulse sequence, with the following parameters: field of view = 120 mm, 16 9 16 matrix with reduced k-space sampling (208 phase encoding steps), 256 points, slice thickness = 2 cm, flip angle = 7°, repetition time = 80 ms, bandwidth = 5,000 Hz.…”
Section: Mr Test Of the Coils In Vivo On Pigmentioning
confidence: 99%
“…As the contrast in FIESTA images is related to the T2-T1 ratio in the tissue, these sequences have been successfully applied to cardiac imaging, to the imaging of cartilage, breast, and fetus. (80)(81)(82)(83)(84) Recently, studies have shown the application of this imaging technique to MR colonography and small bowel enteroclysis. ( 85) Another characteristic of FIESTA imaging is a sharp edge definition, which results paramount during the image segmentations to reduce inconsistencies due to motion blur of the GI wall.…”
Section: Fiesta Imagingmentioning
confidence: 99%